TACTICAL ANALYSIS OF INDONESIAN NATIONAL FOOTBALL TEAM USING FP-TREE ALGORITHM - Ardiantoro , Luki; M. Akbar , Ronny; Nur S., Yanuarini (LPPM Universitas Duta Bangsa Surakarta, 2023)
Football is the most popular sport in the world, including Indonesia. The current coach of the Indonesian national team is Shin Tae-yong (STY), a former South Korean soccer player. In this study, the researcher intends to study and obtain an overview of the game patterns, tactics and game strategies carried out by STY for the Indonesian national team. The goal to be achieved is gained of tactics and strategies for local coaches in the future. Frequent Pattern Tree (FP-Tree) algorithm was used for this research. Method to analyze match videos and record them in the form of statistical data in a set of data modelling (rows/records) for a particular match session, was used. Then normalize the data, by forming a series of pattern numbers as a representation of the direction of attack in certain situation. As conclusion, the national team's playing pattern, including team formation, how to defend, how to attack. Thus, it makes it easier for coaches to determine the right strategy to beat opponents, when dealing in official matches.